2019
DOI: 10.1038/s41598-019-55464-5
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the biology of Mycobacterium mucogenicum and Mycobacterium neoaurum clade members

Abstract: Nontuberculous mycobacteria, NTM, are of growing concern and among these members of the Mycobacterium mucogenicum (Mmuc) and Mycobacterium neoaurum (Mneo) clades can cause infections in humans and they are resistant to first-line anti-tuberculosis drugs. They can be isolated from different ecological niches such as soil, tap water and ground water. Mycobacteria, such as Mmuc and Mneo, are classified as rapid growing mycobacteria, RGM, while the most familiar, Mycobacterium tuberculosis, belongs to the slow gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 94 publications
(125 reference statements)
0
14
0
Order By: Relevance
“…The numbers and types of IS elements, and the presence of phage sequences and plasmids vary among mycobacteria. These and other factors all possibly contribute to the evolution of the genus and bacteria in general (see also Refs [ 6 , 24 , 26 , 27 , 57 ]), e.g., the presence of HNH endonucleases, transposases, RNA elements such as ALIL pseudoknots (required to induce transposition [ 46 , 55 ]), presence/absence of ncRNAs, numbers of tRNA genes, and horizontally transferred genes all possibly contribute to the evolution of the genus and bacteria in general.…”
Section: Discussionmentioning
confidence: 99%
“…The numbers and types of IS elements, and the presence of phage sequences and plasmids vary among mycobacteria. These and other factors all possibly contribute to the evolution of the genus and bacteria in general (see also Refs [ 6 , 24 , 26 , 27 , 57 ]), e.g., the presence of HNH endonucleases, transposases, RNA elements such as ALIL pseudoknots (required to induce transposition [ 46 , 55 ]), presence/absence of ncRNAs, numbers of tRNA genes, and horizontally transferred genes all possibly contribute to the evolution of the genus and bacteria in general.…”
Section: Discussionmentioning
confidence: 99%
“…1 ). In the non-tuberculous mycobacteria, the subsystem classification suggested that 18% of the gene ontologies belong to amino acids and its derivatives category, 12% to Cofactors, vitamins, prosthetic groups and pigments [ 33 ]. The biosynthesis of amino acids and their derivatives greatly determines the survival of bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…This information was gathered for CFP‐10 from M. ulcerans (WP_012392185.1), M. scrofulaceum (ORB70459.1), and M. mucogenicum (WP_061000007.1). To confirm gene duplication events detected in several species, literature reviews were conducted to identify articles that examined gene duplications for the affected species: M. xenopi , [ 27 ] M. kansasii, M. szulgai , and M. marinum , [ 28 ] M. mucogenicum , [ 29 ] M. chelonae , and M. fortuitum . [ 30 ]…”
Section: Methodsmentioning
confidence: 99%